A polyimide composite phenylacetylene copper photocatalyst and its preparation method and application
By combining polyimide with copper phenylacetylene, a polyimide composite copper phenylacetylene photocatalyst is formed, which solves the problem of low pollutant degradation efficiency of existing copper phenylacetylene photocatalysts and significantly improves the ability of photocatalytic degradation of tetracycline. effect.
Patent Information
- Application Number
- CN202310992753.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-08
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure CN117324040B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalysts, and in particular relates to a polyimide composite phenylacetylene copper photocatalyst and a preparation method and application thereof. Background Art
[0002] Since the advent of antibiotics, they have been widely used due to their significant anti-infection effects. Among them, tetracycline has become the most widely used antibiotic in livestock and poultry farming, medical clinics, etc. due to its low cost and good antibacterial activity, and is continuously discharged into water bodies, causing environmental pollution. Tetracycline will have ecotoxic effects on animals, plants, and microorganisms in the environment. At the same time, it will enter the food chain through animal and plant absorption and enrichment, affecting human health, and even induce the production of resistance genes and enhance their spread, ultimately posing a serious threat to public health. The biological treatment process in traditional sewage treatment plants is difficult to remove these antibiotic pollutants, so new technologies need to be developed to solve these problems. Many studies have shown that semiconductor-mediated photocatalytic technology has very good application prospects in many aspects such as the decomposition of organic pollutants. Therefore, it is necessary to develop a new semiconductor photocatalyst to remove tetracycline pollution in water bodies.
[0003] Copper phenylacetylene is a relatively mature photocatalyst with the advantages of strong visible light response, good stability, and strong reducing ability. It can oxidize the chromophore in tetracycline into small molecules such as CO, CO2, and organic acids, thereby destroying the chromophore of tetracycline. However, although copper phenylacetylene has a strong light response ability, its low charge separation and transfer efficiency and rapid photogenerated electron-hole recombination limit its efficiency in photocatalytic degradation of pollutants. Therefore, it is very important to further modify it to improve its photocatalytic performance.
[0004] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention
[0005] The purpose of the present invention is to provide a polyimide composite phenylacetylene copper photocatalyst to solve the problem that the existing phenylacetylene copper photocatalyst has low efficiency in degrading pollutants.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a polyimide composite phenylacetylene copper photocatalyst comprises the following steps:
[0008] S1: dissolving cupric chloride dihydrate in methanol, then adding phenylacetylene and triethylamine while stirring, and heating to react to obtain phenylacetylene copper;
[0009] S2: Grinding and mixing melamine and pyromellitic anhydride uniformly, and heating for reaction to obtain polyimide;
[0010] S3: mixing the copper phenylacetylene prepared in step S1, the polyimide prepared in step S2, the high molecular polymer and the first solvent, collecting the solid after the reaction is completed, washing and drying, to obtain a polyimide composite copper phenylacetylene photocatalyst.
[0011] Preferably, the high molecular polymer is polyvinyl pyrrolidone, and the first solvent is selected from one or more of water, methanol and ethanol.
[0012] Preferably, in step S1, the molar ratio of cupric chloride dihydrate, phenylacetylene and triethylamine is 1:4:2.
[0013] Preferably, in step S2, the molar ratio of melamine to pyromellitic dianhydride is 1:1.
[0014] Preferably, in step S3, the mass ratio of the copper phenylacetylene, polyimide and high molecular polymer is (10-20):(1-14):(20-40).
[0015] Preferably, the first solvent is selected from distilled water, deionized water or ultrapure water.
[0016] Preferably, in step S1, the reaction temperature is 60-80° C., the reaction time is 20-50 min, and after the reaction is completed, the product is collected by centrifugation, washed with water and ethanol 2-3 times in sequence, and dried to obtain the phenylacetylene copper photocatalyst.
[0017] Preferably, in step S2, the heating rate is 4-7°C / min, the reaction temperature is 250-350°C, and the reaction time is 4-6h.
[0018] The present invention also provides a polyimide composite phenylacetylene copper photocatalyst, which is prepared by any of the above methods.
[0019] The present invention also provides the use of the polyimide composite phenylacetylene copper photocatalyst in photocatalytic degradation of tetracycline.
[0020] Beneficial effects:
[0021] (1) The polyimide composite phenylacetylene copper photocatalyst prepared by the present invention enhances the π→π* electron transition effect on the basis of phenylacetylene copper, uses the π-π structure to enhance the delocalization of the photogenerated electrons of phenylacetylene copper, and enhances the π→π* electron transition to regulate the electronic structure of phenylacetylene copper; the two-dimensional planar structure of polyimide provides more active centers for the reaction, creates more transfer channels for photogenerated electrons, and can enhance the adsorption capacity of the material for tetracycline to a certain extent, and has broad application prospects in the fields of environmental pollution control, energy, etc.
[0022] (2) The polyimide composite phenylacetylene copper photocatalyst prepared by the present invention has significantly enhanced the ability of photocatalytic degradation of tetracycline compared with phenylacetylene copper, and can efficiently utilize visible light to catalytically degrade pollutants. In addition, the synthesis method of the photocatalyst is simple, the synthetic materials are easily available, the synthetic reaction conditions are relatively mild, and it is easy to produce and promote. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:
[0024] Figure 1 The experimental results of photocatalytic degradation of tetracycline by PI / PhC2Cu prepared in Example 1 and Comparative Examples 1-4 are shown.
[0025] Figure 2 The experimental results of photocatalytic degradation of organic dyes by PI / PhC2Cu prepared in Example 1.
[0026] Figure 3 This is the Fourier transform infrared analysis spectrum of PI / PhC2Cu prepared in Example 1.
[0027] Figure 4 This is the SEM image of PI.
[0028] Figure 5 This is the SEM image of PI / PhC2Cu prepared in Example 1.
[0029] Figure 6 These are the transient photoresponse current analysis results of PI / PhC2Cu and PhC2Cu and PI prepared in Example 1.
[0030] Figure 7 These are the electrochemical impedance spectroscopy diagrams of PI / PhC2Cu and PhC2Cu and PI prepared in Example 1.
[0031] Figure 8 The photocatalytic degradation effect of PI / PhC2Cu prepared in Example 1 on tetracycline in different anion environments.
[0032] Fig. 9 The photocatalytic degradation effect of PI / PhC2Cu prepared in Example 1 on tetracycline in different cationic environments.
[0033] Fig.10 The photocatalytic degradation effect of PI / PhC2Cu prepared in Example 1 on tetracycline in different pH environments. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0035] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0036] The present invention aims at the problem of low efficiency in the current photocatalytic degradation of tetracycline in water by copper phenylacetylene. The present invention provides a polyimide composite copper phenylacetylene photocatalyst, which uses a π-π structure to enhance the delocalization of photogenerated electrons of copper phenylacetylene, utilizes the two-dimensional planar structure of polyimide to provide more reaction active centers, promotes the transfer of photogenerated electrons, and enhances the adsorption capacity of the material for tetracycline.
[0037] The preparation method of the polyimide composite phenylacetylene copper photocatalyst provided by the present invention comprises the following steps:
[0038] S1: dissolving cupric chloride dihydrate in methanol, then adding phenylacetylene and triethylamine while stirring, and heating to react to obtain phenylacetylene copper;
[0039] S2: Grinding and mixing melamine and pyromellitic anhydride uniformly, and heating for reaction to obtain polyimide;
[0040] S3: mixing the copper phenylacetylene prepared in step S1, the polyimide prepared in step S2, the high molecular polymer and the first solvent, collecting the solid after the reaction is completed, washing and drying, to obtain a polyimide composite copper phenylacetylene photocatalyst.
[0041] In a preferred embodiment of the present invention, the high molecular polymer is polyvinyl pyrrolidone, and the first solvent is selected from one or more of water, methanol and ethanol.
[0042] In a preferred embodiment of the present invention, in step S1, the molar ratio of cupric chloride dihydrate, phenylacetylene and triethylamine is 1:4:2.
[0043] In a preferred embodiment of the present invention, in step S2, the molar ratio of melamine to pyromellitic dianhydride is 1:1.
[0044] In a preferred embodiment of the present invention, in step S3, the mass ratio of copper phenylacetylene, polyimide and high molecular polymer is (10-20):(1-14):(20-40).
[0045] In a preferred embodiment of the present invention, the first solvent is selected from distilled water, deionized water or ultrapure water.
[0046] In a preferred embodiment of the present invention, in step S1, the reaction temperature is 60-80° C., and the reaction time is 20-50 min.
[0047] In a preferred embodiment of the present invention, in step S2, the heating rate is 4-7°C / min, the reaction temperature is 250-350°C, and the reaction time is 4-6h.
[0048] The present invention also provides the use of the polyimide composite phenylacetylene copper photocatalyst in photocatalytic degradation of tetracycline to replace the existing phenylacetylene copper photocatalyst.
[0049] The following is a detailed description of a polyimide composite phenylacetylene copper photocatalyst and its preparation method and application according to the present invention through specific embodiments.
[0050] The raw materials used in the following examples are as follows:
[0051] Copper chloride dihydrate: analytical grade, purchased from Aladdin Company.
[0052] Triethylamine: analytical grade, purchased from Aladdin Company.
[0053] Phenylacetylene: analytical grade, purchased from Maclean Company.
[0054] Methanol: analytical grade, purchased from Aladdin Company.
[0055] Melamine: analytical grade, purchased from Aladdin Company.
[0056] Pyromellitic anhydride: analytical grade, purchased from Maclean Company.
[0057] Polyvinyl pyrrolidone: analytical grade, purchased from Aladdin Company.
[0058] Ethanol: analytical grade, purchased from Aladdin Company.
[0059] Example 1
[0060] This embodiment provides a polyimide composite phenylacetylene copper photocatalyst, and the preparation method of the photocatalyst comprises the following steps:
[0061] S1. Preparation of phenylacetylene copper photocatalyst (PhC2Cu):
[0062] S11. Add 0.547 g of cupric chloride dihydrate (0.003 mol) into a beaker and dissolve it in 50 mL of methanol. After the cupric chloride dihydrate is completely dissolved, add 1.68 mL of triethylamine (0.012 mol) and 0.66 mL of phenylacetylene (0.003 mol) in sequence while stirring the liquid.
[0063] S12, reacting the mixed liquid in a water bath at 70°C for 30 minutes to generate yellow floccules.
[0064] S13. The yellow flocculants were collected by centrifuge at 10000 r / min, washed twice with pure water and ethanol, and dried in an oven at 60° C. for 10 h to obtain a yellow solid, which was a phenylacetylene copper photocatalyst.
[0065] S2. Preparation of polyimide (PI):
[0066] S21. Put 1.261 g of melamine (0.010 mol) and 2.181 g of pyromellitic dianhydride (0.010 mol) in a mortar and grind and mix.
[0067] S22. The ground powder is transferred into a crucible, and heated to 250°C in a muffle furnace at a heating rate of 7°C / min for 4 hours to obtain a white powder.
[0068] S23, washing the white powder with pure water at 55° C. for three times, and then drying it in an oven at 60° C. for 10 hours. The obtained white powder is polyimide PI.
[0069] S3. Preparation of polyimide composite phenylacetylene copper photocatalyst:
[0070] S31. Dissolve 0.03 g of the polyimide prepared in step S1 and 0.2 g of polyvinyl pyrrolidone in 50 mL of pure water under ultrasound.
[0071] S32. After the PI powder is evenly dispersed, add 0.1 g of PhC2Cu obtained in step S2, and mix and react for 5 minutes under ultrasound.
[0072] S33. Collect the reaction product using a centrifuge at a speed of 10000 r / min, wash it twice with pure water and ethanol, and bake it in an oven at 60° C. for 10 h to obtain a polyimide composite phenylacetylene copper photocatalyst PI / PhC2Cu.
[0073] Example 2
[0074] Preparation of PhC2Cu photocatalyst:
[0075] S11. Add 0.547 g of cupric chloride dihydrate (0.003 mol) into a beaker and dissolve it in 50 mL of methanol. After the cupric chloride dihydrate is completely dissolved, add 1.68 mL of triethylamine (0.012 mol) and 0.66 mL of phenylacetylene (0.003 mol) in sequence while stirring the liquid.
[0076] S12, reacting the mixed liquid in a water bath at 60°C for 35 minutes to generate yellow floccules.
[0077] S13. The yellow floccules were collected by using a centrifuge at 10000 r / min, washed three times with pure water and ethanol, and heated in an oven at 60° C. for 10 h to obtain the PhC2Cu photocatalyst.
[0078] Example 3
[0079] Preparation of PhC2Cu photocatalyst:
[0080] S11. Add 0.182 g of cupric chloride dihydrate (0.001 mol) into a beaker and dissolve it in 50 mL of methanol. After the cupric chloride dihydrate is completely dissolved, add 1.68 mL of triethylamine (0.004 mol) and 0.66 mL of phenylacetylene (0.001 mol) in sequence while stirring the liquid.
[0081] S12, reacting the mixed liquid in a water bath at 80°C for 25 minutes to generate yellow floccules.
[0082] S13. The yellow floccules were collected by using a centrifuge at 10000 r / min, washed three times with pure water and ethanol, and heated in an oven at 60° C. for 10 h to obtain the PhC2Cu photocatalyst.
[0083] Example 4
[0084] Preparation of polyimide:
[0085] S21. Grind and mix 1.261 g of melamine and 2.181 g of pyromellitic dianhydride in a mortar.
[0086] S22. The ground powder is transferred into a crucible, and heated to 350°C in a muffle furnace at a heating rate of 4°C / min for 5 hours to obtain a white powder.
[0087] S23, washing the white powder with pure water at 55° C. for 4 times, and drying the powder in an oven at 60° C. for 10 hours to obtain polyimide.
[0088] Example 5
[0089] Preparation of polyimide:
[0090] S21. Grind and mix 1.261 g of melamine and 2.181 g of pyromellitic dianhydride in a mortar.
[0091] S22. The ground powder is transferred into a crucible, and heated to 300°C in a muffle furnace at a heating rate of 6°C / min for 6 hours to obtain a white powder.
[0092] S23, washing the white powder with pure water at 55° C. for three times, and drying the powder in an oven at 60° C. for 10 hours to obtain polyimide.
[0093] Example 6
[0094] Preparation of polyimide composite phenylacetylene copper photocatalyst:
[0095] The PhC2Cu photocatalyst prepared in Example 2 and the polyimide prepared in Example 4 were used to replace the PhC2Cu photocatalyst and polyimide prepared in Example 1, and other conditions remained unchanged to prepare a polyimide composite phenylacetylene copper photocatalyst.
[0096] Example 7
[0097] Preparation of polyimide composite phenylacetylene copper photocatalyst:
[0098] The PhC2Cu photocatalyst prepared in Example 2 and the polyimide prepared in Example 5 were used to replace the PhC2Cu photocatalyst and polyimide prepared in Example 1, and other conditions remained unchanged to prepare a polyimide composite phenylacetylene copper photocatalyst.
[0099] Example 8
[0100] Preparation of polyimide composite phenylacetylene copper photocatalyst:
[0101] The PhC2Cu photocatalyst prepared in Example 3 and the polyimide prepared in Example 4 were used to replace the PhC2Cu photocatalyst and polyimide prepared in Example 1, and other conditions remained unchanged to prepare a polyimide composite phenylacetylene copper photocatalyst.
[0102] Example 9
[0103] Preparation of polyimide composite phenylacetylene copper photocatalyst:
[0104] The PhC2Cu photocatalyst prepared in Example 3 and the polyimide prepared in Example 5 were used to replace the PhC2Cu photocatalyst and polyimide prepared in Example 1, and other conditions remained unchanged to prepare a polyimide composite phenylacetylene copper photocatalyst.
[0105] Comparative Example 1
[0106] In this comparative example, based on Example 1, the amount of PI in step S31 was adjusted to 0.01 g, and the remaining steps were consistent with Example 1, and PI / PhC2Cu 10% was obtained by reaction.
[0107] Comparative Example 2
[0108] In this comparative example, based on Example 1, the amount of PI in step S31 was adjusted to 0.02 g, and the remaining steps were consistent with Example 1, and PI / PhC2Cu 20% was obtained by reaction.
[0109] Comparative Example 3
[0110] In this comparative example, based on Example 1, the amount of PI in step S31 was adjusted to 0.03 g, and the remaining steps were consistent with Example 1, and PI / PhC2Cu 30% was obtained by reaction.
[0111] Comparative Example 4
[0112] In this comparative example, based on Example 1, the amount of PI in step S31 was adjusted to 0.04 g, and the remaining steps were consistent with Example 1, and the reaction produced PI / PhC2Cu 40%.
[0113] Comparative Example 5
[0114] The comparative example of the present application uses another phenylacetylene copper photocatalyst to synthesize the composite photocatalyst, comprising the following steps:
[0115] S1. Preparation of PhC2Cu:
[0116] S11. Dissolve 0.547 g CuCl2·H2O in 60 mL of methanol, and add 1.68 mL of triethylamine and 0.66 mL of phenylacetylene to the mixture to obtain a mixed solution.
[0117] S12. The above liquid was reacted under stirring for 1.5 h to obtain a yellow precipitate.
[0118] S13. The generated yellow precipitate is collected by centrifugation, washed twice with ethanol, and dried to obtain one-step PhC2Cu.
[0119] S2. Preparation of polyimide:
[0120] S21. Grind and mix 1.261 g of melamine and 2.181 g of pyromellitic anhydride in a mortar.
[0121] S22. The ground powder was transferred into a crucible and heated to 250°C in a muffle furnace at a heating rate of 7°C / min for 4 h to obtain a white powder.
[0122] S23, washing the white powder with 55° C. pure water for 3 to 4 times, and drying it in an oven at 60° C. The drying time is 10 h to obtain polyimide.
[0123] S3. Preparation of PhC2Cu / PI photocatalyst by one-step method:
[0124] S31. Dissolve 0.1 g of the one-step PhC2Cu prepared in step S1, 0.2 g of polyvinyl pyrrolidone, and 0.03 g of the polyimide prepared in step S2 in 50 mL of pure water to obtain a mixed solution.
[0125] S32, subjecting the mixed solution to ultrasonic mixing for 5 min.
[0126] S33. Collect the reaction product using a centrifuge at 10,000 r / min, wash it with pure water and ethanol three times, and bake it in an oven at 60°C for 10 h to obtain a one-step PhC2Cu / PI photocatalyst.
[0127] Evaluation of the effect of photocatalytic degradation of tetracycline:
[0128] Experimental protocol:
[0129] 1. Weigh 10 mg of the prepared PI / PhC2Cu photocatalyst powder and add it into 50 mL of tetracycline solution (concentration is 20 mg / L);
[0130] 2. Before the photocatalytic reaction, a dark reaction was performed for 30 minutes. After the material and tetracycline were in adsorption equilibrium, a 9W LED light was used to react for 15 minutes. After sampling, the residual concentration C of tetracycline in the solution was determined using a high performance liquid chromatograph;
[0131] 3. Calculate the removal rate of tetracycline by polyimide composite phenylacetylene copper photocatalyst. The calculation formula is: , where C0 is the initial concentration of tetracycline and C is the residual concentration.
[0132] Evaluation of photocatalytic degradation of organic dyes:
[0133] Experimental protocol:
[0134] 1. Weigh 10 mg of PI / PhC2Cu photocatalyst powder and add 50 mL of methyl orange, methylene blue, naphthol green, and methyl violet solution (all with a concentration of 5 mg / L);
[0135] 2. Before the photocatalytic reaction, a dark reaction was performed for 30 min. After the material and tetracycline were adsorbed to equilibrium, a 9W LED light was used to react for 40 min. After sampling, the absorbance A of the dye solution in the solution was measured using a UV-visible spectrophotometer.
[0136] 3. Calculate the removal rate of four dyes by polyimide composite phenylacetylene copper photocatalyst. The calculation formula is: , where A0 is the initial absorbance and A is the absorbance of the liquid after the reaction.
[0137] Taking Example 1 as an example, the above scheme was used to test the effect of the polyimide composite phenylacetylene copper photocatalyst prepared in the embodiment of the present invention and the comparative example, wherein: Figure 1 The experimental results of photocatalytic degradation of tetracycline by PI / PhC2Cu photocatalysts prepared in Example 1 and Comparative Examples 1 to 4 are shown. It can be clearly seen from the figure that after the reaction starts, the PI / PhC2Cu photocatalyst prepared in Example 1 can quickly reduce the concentration of tetracycline in the solution. After 5 minutes of reaction, the concentration of tetracycline in the solution has dropped to less than 50% of the initial concentration C0, and the degradation rate is significantly higher than that of PI and PhC2Cu. When the reaction is continued for 15 minutes, the PI / PhC2Cu photocatalyst prepared in Example 1 can reduce the concentration of tetracycline to less than 20% at different concentrations, while the PhC2Cu photocatalyst can only reduce it to about 35%. It can be seen that the catalytic efficiency of the composite photocatalyst obtained by compounding the PhC2Cu photocatalyst with PI is significantly improved.
[0138] Figure 2 The degradation rates of methyl orange, methylene blue, naphthol green and methyl violet of the PI / PhC2Cu photocatalyst prepared in Example 1 after 40 minutes of reaction are as shown in the figure. The degradation rate of methyl violet by the PI / PhC2Cu photocatalyst can reach 97.71%, and the degradation effect on methylene blue is the worst, but can also reach about 50%. Overall, the PI / PhC2Cu photocatalyst has a significant degradation effect on organic dyes.
[0139] The PI / PhC2Cu photocatalyst prepared in Example 1 was subjected to infrared analysis. Figure 3 As shown, characteristic peaks of PI and PhC2Cu appeared on the spectrum of PI / PhC2Cu photocatalyst, indicating that PI and PhC2Cu were successfully compounded into PI / PhC2Cu.
[0140] The PI and the PI / PhC2Cu photocatalyst prepared in Example 1 were detected by scanning electron microscopy, wherein PI was Figure 4 As shown, it has a two-dimensional sheet structure; PI / PhC2Cu photocatalyst Figure 5 As shown in the figure, PhC2Cu nanowires and two-dimensional sheet-like PI are criss-crossed with each other, and some shorter PhC2Cu nanowires are tightly attached to PI, indicating that there is a very strong interaction force between PI / PhC2Cu, and the criss-crossed structure is more conducive to electron transfer between materials.
[0141] Figure 6The transient photoresponse current analysis of PI / PhC2Cu, PhC2Cu and PI prepared in Example 1 is shown in the figure. As shown in the figure, PI / PhC2Cu has a much higher photocurrent density than PhC2Cu and PI, indicating that PI / PhC2Cu has a stronger photocharge response ability than PhC2Cu and PI under a low-power LED lamp of 9 W.
[0142] Figure 7 The electrochemical impedance spectroscopy of PI / PhC2Cu, PhC2Cu and PI prepared in Example 1 is shown in the figure. As shown in the figure, PI / PhC2Cu has a significantly smaller arc radius than PhC2Cu and PI, which indicates that the PI / PhC2Cu material has a smaller charge transfer resistance.
[0143] The photocatalytic effect of PI / PhC2Cu on tetracycline under different anion and cation and pH environments was tested as follows:
[0144] The photocatalytic degradation effect of tetracycline by PI / PhC2Cu prepared in Example 1 was tested under different anion environments. Figure 8 As shown, CO3 2- 、HCO2 - , Cl - 、SO4 2 These anions have no significant effect on the photocatalytic effect of PI / PhC2Cu prepared in Example 1, while CO3 2- 、HCO2 - It can promote the photocatalytic effect of PI / PhC2Cu.
[0145] The photocatalytic degradation effect of tetracycline by PI / PhC2Cu prepared in Example 1 was tested under different anion environments. Fig. 9 As shown, humic acid (HA), Ca 2+ Mg 2+ , Fe 2+ These cations have no obvious effect on the photocatalytic degradation of tetracycline by PI / PhC2Cu.
[0146] The photocatalytic degradation effect of tetracycline by PI / PhC2Cu prepared in Example 1 was tested in water environments with different pH values. Fig.10 As shown, the pH of the water body has little effect on the photocatalytic degradation of tetracycline by PI / PhC2Cu, among which the efficiency of photocatalytic degradation of tetracycline by PI / PhC2Cu at pH=9 is significantly improved compared with that at pH=7.
[0147] It can be seen that the PI / PhC2Cu photocatalyst can adapt to a variety of complex usage environments, is not easily affected by common anions and cations in water, and exhibits stable photocatalytic effects in both acidic and alkaline environments.
[0148] In summary, the PI / PhC2Cu photocatalyst prepared by the present invention can have a significant catalytic effect on the photocatalytic degradation of tetracycline and organic dyes, and has good adaptability to a variety of anions and cations and a wide pH range. Its catalytic effect is not easily interfered by other factors in the environment, and is very suitable for the degradation of pollutants such as tetracycline and organic dyes in water bodies.
[0149] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. Use of a polyimide composite phenylacetylene copper photocatalyst in photocatalytic degradation of tetracycline, characterized in that: The preparation method of the polyimide composite phenylacetylene copper photocatalyst comprises the following steps: S1: dissolving cupric chloride dihydrate in methanol, then adding phenylacetylene and triethylamine while stirring, and heating to react to obtain phenylacetylene copper; S2: Grinding and mixing melamine and pyromellitic anhydride uniformly, and heating for reaction to obtain polyimide; S3: mixing the copper phenylacetylene prepared in step S1 and the polyimide prepared in step S2 with polyvinyl pyrrolidone and a first solvent, wherein the mass ratio of the copper phenylacetylene, the polyimide and the high molecular polymer is (10-20):(1-14):(20-40). After the reaction is completed, the solid is collected, washed and dried to obtain a polyimide composite copper phenylacetylene photocatalyst; The first solvent is selected from one or more of water, methanol and ethanol.
2. Use of a polyimide composite phenylacetylene copper photocatalyst in photocatalytic degradation of tetracycline as claimed in claim 1, characterized in that: In step S1, the molar ratio of cupric chloride dihydrate, phenylacetylene and triethylamine is 1:1:
4.
3. Use of a polyimide composite phenylacetylene copper photocatalyst in photocatalytic degradation of tetracycline as claimed in claim 1, characterized in that: In step S2, the molar ratio of melamine to pyromellitic anhydride is 1:
1.
4. Use of a polyimide composite phenylacetylene copper photocatalyst in photocatalytic degradation of tetracycline as claimed in claim 1, characterized in that: The first solvent is selected from distilled water, deionized water or ultrapure water.
5. Use of a polyimide composite phenylacetylene copper photocatalyst as claimed in any one of claims 1 to 4 in photocatalytic degradation of tetracycline, characterized in that: In step S1, the reaction temperature is 60-80° C., the reaction time is 20-50 min, and after the reaction is completed, the product is collected by centrifugation, washed with water and ethanol 2-3 times in sequence, and dried to obtain the phenylacetylene copper photocatalyst.
6. Use of a polyimide composite phenylacetylene copper photocatalyst as claimed in any one of claims 1 to 5 in photocatalytic degradation of tetracycline, characterized in that: In step S2, the heating rate is 4-7°C / min, the reaction temperature is 250-350°C, and the reaction time is 4-6h.
Citation Information
Patent Citations
Silver phosphate and conjugated polymer visible light composite photocatalyst
CN105709831A
Photocatalyst supported micro-nano-composite fiber material loaded and preparation method thereof
CN109126881A